Museum and school partnership for learning on field trips - Bhatia, Anuradha, author; Makela, Carole J., advisor; Sarkar, Ajoy Kumar, advisor; Loomis, Ross J., committee member; Wallner, Barbara, committee member (Colorado State University. Libraries, 2009)
School field trips are the most common type of partnership between museums and schools. Museums of all specialties offer programs to children of all ages/grades keeping their physical, intellectual, and cognitive development in mind. By partnering with schools, museums support curriculum standards and supplement classroom teaching. The purpose of this phenomenology was to explain the partnership between a local history museum, the Fort Collins Museum (FCM), and Poudre School District’s (PSD) schools for learning on 2nd grade field trips. Museum educators and school teachers are the representatives of the two institutions. Their perceptions and processes regarding museum field trip delivery and integration were studied and the partnership was explained on the basis of purpose and level of interactions.
Department Head: Timothy Gray Davies.